The Optimal Treatment for Resectable Esophageal Cancer: A Network Meta-Analysis of 6168 Patients - Yuan, Meng; Bao, Yongxing; Ma, Zeliang; Men, Yu; Wang, Yang; Hui, Zhouguang (Frontiers in Oncology, 2021)
The optimal treatment for resectable esophageal cancer remains unclear. This network meta-analysis is to compare the efficacy of different treatments. PubMed, Embase and Cochrane library were systematically screened. The randomized controlled trials (RCT) comparing the efficacy of different treatments for resectable esophageal cancer were included. Hazard ratios (HR) for overall survival (OS), progression free survival (PFS) or disease free survival (DFS), and odds ratios (OR) for locoregional recurrence and distant metastasis rate were identified as the measurements of efficacy. Bayesian network meta-analysis was performed. In this study, twenty-six studies were included. Patients received either surgery alone, or neoadjuvant CT, neoadjuvant RT or neoadjuvant CRT followed by surgery, or surgery followed by adjuvant CT, adjuvant RT or adjuvant CRT. Neoadjuvant CRT followed by surgery (pooled HR=0.76, 95% credible interval (CrI): 0.67-0.85) and neoadjuvant CT followed by surgery compared with surgery alone were the only two showing statistically confident improvement on OS. Ranking analysis showed that neoadjuvant CRT with surgery was likely to be the best option in terms of efficacy. Therefore, for patients with resectable esophageal cancer, neoadjuvant CRT with surgery is the optimal treatment. Future studies should focus on the optimization of neoadjuvant CRT regimens.